Trends in alcohol drinking among university students at the Polish University of Warmia and Mazury in Olsztyn. Issue 5 (October 2017) - Podstawski, Robert; Wesołowska, Elżbieta; Choszcz, Dariusz
Aim: This article presents cross-sectional data collected from the population of first-year students at the University of Warmia and Mazury in Olsztyn in 2000–2016. The aim of the study was to investigate changes in the following trends among university students after Poland's accession to the European Union (2004): (1) alcohol consumption, (2) alcoholic beverage preferences, and (3) attitudes towards alcohol. Method: The study relied on data from anonymous surveys conducted every two years between 2000 and 2016 among a representative sample of first-year university students. A total of 9778 individuals (4264 males and 5514 females) completed anonymous questionnaires during the period under analysis. Statistical analyses were performed by comparing the frequency of answers given by male and female students in the first and last year of the study. Results: There was a steady linear decrease in the percentages of abstainers of both genders and a regular linear increase in the number of female students abusing alcohol to blackout level in the analysed period of 2000 to 2016. The respondents' preferences for alcohol brands became more diversified (with foreign types of strong liquors becoming more popular), and their attitudes towards alcohol availability on campus were liberalised. Conclusions: Our data complement the gaps in empirical research on alcohol consumption among university students in European countries. They point to greater homogenisation of Polish drinking culture and convergence in male and female drinking behaviours.